Rethinking the Faster R-CNN Architecture for Temporal Action Localization - Chao, Yu-Wei; Vijayanarasimhan, Sudheendra; Seybold, Bryan; Ross, David A.; Deng, Jia; Sukthankar, Rahul (2018 IEEE/CVF Conference on Computer Vision and Pattern Recognition, 2018)
We propose TAL-Net, an improved approach to temporal action localization in video that is inspired by the Faster RCNN object detection framework. TAL-Net addresses three key shortcomings of existing approaches: (1) we improve receptive field alignment using a multi-scale architecture that can accommodate extreme variation in action durations; (2) we better exploit the temporal context of actions for both proposal generation and action classification by appropriately extending receptive fields; and (3) we explicitly consider multi-stream feature fusion and demonstrate that fusing motion late is important. We achieve state-of-the-art performance for both action proposal and localization on THUMOS'14 detection benchmark and competitive performance on ActivityNet challenge.